(untitled) (Journal of Oriental Studies, 2019)
This article discusses the role of literature at the present stage of society’s development and its role in the formation of the spiritual and moral foundations of the student’s personality. Spiritual and moral education, the formation and knowledge of oneself, to live not only for yourself, but also for others. It is considered through the comprehension of national codes in (Korean) literature. The search for the mean ing of the life of the young generation manifested in public life in the context of chronic anomie (lack of a norm) acquires particular urgency in the era of globalization. There are typical features of anomia as follows: disintegration of traditional value systems; blurring the boundary between what is permitted and forbidden; lack of culture of freedom; inability to take responsibility for their actions; desire for mimicry; growth of selfishness; the extinction of feelings of community, social responsibility and solidarity. Next to this agony of individualism, cruel capital is pushing for social death. The meaning of life for a lonely man, for a stranger among his own, for the hero of the Cho Jung Rae’s story named “Human’s destiny” becomes lonely children as he is. Now they have a grandfather who will take care of them, and there are children who will take care of him. Key words: national values, national traditions, personality destruction, existential vacuum.